(untitled) (Medical Forum Monthly, 2024)
Objective: To measure anatomical factors particularly in relation to the lower pole calyceal anatomy of normal healthy kidneys in our population in order to find their clinical significance. Study Design: Observational / Cross-sectional study Place and Duration of Study: This study was conducted at the. Department of Anatomy, Watim Dental College, Rawat, Department of Urology, Shaafi International Hospital, Islamabad and Department of Radiology, Al-Nafees Medical College & Hospital, Islamabad from July 2015 to April 2017. Materials and Methods: 25 healthy kidney donors between 18 – 60 years aged, who were referred to the kidney transplant service at Shaafi International Hospital, Islamabad having normal renal function, coming through ethical and official processes of kidney donation, and submitting a written consent were included. A total of 50 kidneys (from 25 IVU films) were available for the purpose of this study. The source of IVU films was from Radiology department. The data was collected using predesigned, pretested Pro-forma. The parameters measured were Lower Calyceal Infundibular Length (LCIL), Lower Calyceal Infundibular Width (LCIW) and Lower calyceal infundibulo – ureteropelvic angle (LCIUPA). Obtained data was presented as range, mean ± standard deviation, and percentage (%) distribution. Microsoft Excel program version 2016 was used for statistical analysis. Results: The mean age was 26.9 ± 6.8 years (minimum age was 20 years and maximum age was 41years). The mean LCIL was 26.9 ± SD of 6.8 and mean LCIW was 8.6 ± SD of 2.4. The mean LIUPA was 53.6 ± SD of 23.3. Conclusion: Measurement of lower calyceal anatomical factors is essential in order to identify favourable and unfavourable factors in management of lower calyceal renal stones. Knowledge of these factors is of immense value in deciding best method of treatment of lower calyceal stones in a patient for a successful outcome. Further studies are needed in a 3 dimensional views of renal pelvicalyceal anatomy in order to reflect the data more accurately.